Prediction of immunotherapy response of bladder cancer with a pyroptosis-related signature indicating tumor immune microenvironment - Xu, Zihan; Zhao, Yujie; Zhang, Yong; Liu, Xiaowei; Song, Linlin; Chen, Meixu; Xiao, Guixiu; Ma, Xuelei; Shi, Hubing (Frontiers in Pharmacology, 2024)
BACKGROUND: Although prognostic models based on pyroptosis-related genes (PRGs) have been constructed in bladder cancer (BLCA), the comprehensive impact of these genes on tumor microenvironment (TME) and immunotherapeutic response has yet to be investigated. METHODS: Based on expression profiles of 52 PRGs, we utilized the unsupervised clustering algorithm to identify PRGs subtypes and ssGSEA to quantify immune cells and hallmark pathways. Moreover, we screened feature genes of distinct PRG subtypes and validated the associations with immune infiltrations in tissue using the multiplex immunofluorescence. Univariate, LASSO, and multi-variate Cox regression analyses were employed to construct the scoring scheme. RESULTS: Four PRG clusters were identified, samples in cluster C1 were infiltrated with more immune cells than those in others, implying a favorable response to immunotherapy. While the cluster C2, which shows an extremely low level of most immune cells, do not respond to immunotherapy. CXCL9/CXCL10 and SPINK1/DHSR2 were identified as feature genes of Cluster C1 and C2, and the specimen with high CXCL9/CXCL10 was characterized by more CD8+ T cells, macrophages and less Tregs. Based on differentially expressed genes (DEGs) among PRGs subtypes, a predictive model (termed as PRGs score) including five genes (CACNA1D, PTK2B, APOL6, CDK6, ANXA2) was built. Survival probability of patients with low-PRGs score was significantly higher than those with high-PRGs score. Moreover, patients with low-PRGs score were more likely to benefit from anti-PD1/PD-L1 regimens.CONCLUSION: PRGs are closely associated with TME and oncogenic pathways. PRGs score is a promising indi-cator for predicting clinical outcome and immunotherapy response.